2014
DOI: 10.1515/jpm-2013-0347
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations of activity restriction in high-risk pregnancy scenarios: a Danish national survey

Abstract: Danish obstetricians and midwives prescribe activity restriction in most high-risk pregnancies. The degree of activity restriction and the presumed effect vary between clinicians. This may reflect different attitudes and lack of guidelines based on clinical studies of a possible benefit of activity restriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 37 publications
0
13
0
2
Order By: Relevance
“… 33 37 This is in accordance with a previous study demonstrating that women with poor social support were more often recommended for AOH by health care professionals. 38 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 33 37 This is in accordance with a previous study demonstrating that women with poor social support were more often recommended for AOH by health care professionals. 38 …”
Section: Discussionmentioning
confidence: 99%
“… 22 Activity restriction is often prescribed in cases of threatened preterm delivery; however, it is not registered with a specific treatment code in any of the Danish registries. 12 , 38 , 42 Thus, it is not possible to explicitly study the extent of pregnancy-related activity restriction at Danish hospitals within obstetric services. Even though the AOH rate as well as the number of antenatal threatened preterm delivery hospitalizations decreased, many pregnant women still endure activity restriction either during AOHs or at home without a documented beneficial effect of such an intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2015 Danish survey to over 900 providers found that more often activity restriction in high-risk pregnancies was prescribed by midwives or nurse practitioners, which is not consistent with our discovered prescribing habits but comes from the perspective of providers. 13 Significantly, over half of these high-risk women were placed on complete bed rest and more than two-thirds of women were placed on more than one type of activity restriction, which is demonstrated to be interruptive of multiple aspects of life based, as almost half of these women reported an effect on their quality of life. Similarly, a 1998 survey of maternal-fetal medicine and obstetrician/gynecologist providers demonstrated that bed rest was the most commonly prescribed activity restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Παράλληλα με την βελτιστοποίηση του γλυκαιμικού ελέγχου είναι σημαντικό να υιοθετηθεί ένας υγιεινός τρόπος ζωής ώστε να ελαχιστοποιηθεί ο κίνδυνος επιπλοκών και να ενισχυθεί η υγεία και η καλή ανάπτυξη του εμβρύου. (Bendix et al, 2015).…”
Section: διατροφή και άσκησηunclassified